تأثير طرق عصر ثمار الزيتون على كمية الزيت ونوعيته - ابراهيم دعد معين; سليمان وردة محسن (Latakia University Journal -Biological Sciences Series, 2014)
هدف البحث إلى دراسة تأثير طرق عصر ثمار الزيتون على كمية الزيت ونوعيته، وبينت النتائج الآتي: تؤثر طرق عصر ثمار الزيتون على كمية الزيت بشكل واضح، وقد تميزت الطرق الآلية ونصف الآلية بالنسبة إلى الطريقة التقليدية، وفي المعاصر الآلية زادت كمية الزيت بالنسبة للشاهد (الطريقة التقليدية) بمقدار 60%، وبمقدار 27% بالنسبة للمعاصر نصف الآلية، والعصر بالمعاصر نصف الآلية زاد من كمية الزيت بالنسبة للشاهد بمقدار 28%، وهذا يشير إلى أن العصر بالطريقة الآلية هو أفضل من حيث كمية الإنتاج بالمقارنة مع الطريقة نصف الآلية، والتقليدية. لطريقة عصر الزيتون تأثير على نوعية زيت الزيتون الناتج، حيث أن نوعية الزيت الناتج من عصر ثمار الزيتون في المعصرة الآلية تفوقت على نوعية الزيت الناتج من المعصرة النصف آلية والتقليدية، حيث كانت نكهتها ولونها أفضل، وقرينة حموضتها أقل، وقرينة البيروكسيد فيها أقل، وبالتالي النوعية أفضل. The research was aimed to study the effect of olive press methods on the oil quantity and quality. The results showed the following: The method of press Olive effect to the quantity of Olive oil so the results of oil quantity from olive fruite press in mechanical olive press method more above from half mechanical method and from traditional method ( the witness). The increase of quantity between mechanical and traditional method was 60% and between mechanical half mechanical method was 27% and bween half mechanical and traditional method was 28%. The method of press Olive effect to the of Olive oil quantitatively the results of oil quantitatively from olive fruit press in mechanical olive press machines to surpass half mechanical olive press that is the flavor and color best and Acidity presumption and peroccid number is less .